Farewell to Manzanar - Houston, Jeanne Wakatsuki; Houston, James D. (New York : Bantam, 1974)
Biography of Jeanne Wakatsuki Houston relating her experiences of living at the Manzanar internment camp during World War II and how it has influenced her life.
"A true story of Japanese American experience during and after the World War II internment.".
Book Links (A.L.A.).
Booklist.
Wilson's Junior High School.
8.5
Young Adult.
Keywords: Houston, Jeanne Wakatsuki; Houston, Jeanne Wakatsuki; Manzanar War Relocation Center; Manzanar War Relocation Center; Japanese Americans -- Evacuation and relocation, 1942-1945 -- Biography; Japanese Americans -- Biography